Single-port laparoscopic sacrospinous ligament suspension via the natural vaginal cavity (SvNOTES) for pelvic prolapse: The first feasibility study - Lyu, Yuanyuan; Ding, Huafeng; Ding, Jin; Luo, Yonghong; Guan, Xiaoming; Ni, Guantai (Frontiers in Surgery, 2022)
Objective: To investigate the feasibility and short-term efficacy of single-port laparoscopic-assisted transvaginal natural cavity endoscopic sacrospinous ligament suspensions (SvNOTES). Methods: 30 patients diagnosed with anterior or/and middle pelvic organ prolapse stagesIII-IV underwent natural vaginal cavity(SvNOTES), and 30 patients who underwent conventional sacrospinous ligament (SSLF) were used as a control group. Operative time, blood loss, postoperative POP-Q score, length of hospital stay, and complications were compared between the two groups. Results: The operation time for SvNOTE was (60± 13) minutes, which was longer than SSLF (30±15) minutes(p = 0.04). However, bleeding amount in SvNOTE was 29.44 ± 2.56, significantly lower than that of the SSLF group (80 ± 10; p= 0.02); and the postoperative hospital stay in the Sv-NOTE group was (4 ± 2) days, longer than that of SSLF (3±1) days;(p= 0.02).However, there were no intraoperative complications in the SvNOTE group, whereas one ureteral injury occurred in the SSLF group; in addition, in both groups, the postoperative POP-Q score was significantly better in the SvNOTE group than in the SSLF group with increasing time (P < 0.001). Conclusion： Compared with SSLF, single-port laparoscopic sacrospinous ligament suspension via the natural vaginal cavity is visualized, greatly improving the success rate of sacrospinous ligament fixation, with less blood loss and fewer complications, arguably a safer, minimally invasive surgical approach . Keyword: single-port laparoscopic, natural vaginal cavity , sacrospinal ligament, Pelvic floor dysfunction (PFD); surgery ;